Food and Nutritional Security Through Nutrition Gardening in Unnao District - Singh, Archana; Singh, A.K.; Singh, S.K.; Singh, Sunil; Sahay, Ratna; Tiwari, D.K.; Maurya, R.C. (Indian Journal of Extension Education, 2019)
Malnutrition is a serious public health problem in rural areas of India. In Unnao district of Uttar Pradesh more than 90 per cent farmers have small and marginal land holdings and are unable to meet out daily recommended requirement of fruits and vegetables. Hence most of them are victims of malnutrition specially micronutrient deficiency. To overcome these problem 30 demonstrations of Nutrition Gardening during 2015-16, 2016-17 and 2017-18 were conducted in adopted villages with the objectives to assess the vegetable production from 150 m2 area, availability of vegetables from nutrition garden to different family size and impact of nutrition gardening on food consumption pattern of the respondents. Planned layout was designed and year calendar was followed for round the year availability of fruits and vegetables through nutrition garden. Improved variety of seed and seedlings were provided to the beneficiaries. The results shows that the beneficiaries were growing 10-14 vegetables in planned nutrition garden at a time as compare to 3-6 vegetables in earlier practice. It was also recorded that demonstration results an increase in homestead vegetable production as compare to check and food consumption pattern of vegetables of respondents improved. The results also revealed that 150 m2 area of planned nutrition garden is appropriate to medium size family. It can be concluded from the findings that Nutrition garden is one of the easiest ways of ensuring access to a healthy diet. Thus large scale promotion of Nutrition gardening is needed for nutritional security of the rural households.
Keywords: Demonstration; Malnutrition; Micronutrient deficiency; Nutrition garden; Nutritional security